FRI0483 Do Dermatomyositis and Polymyositis Affect Different Thigh Muscle Groups? A Comparative MRI-Based Study. (9th June 2015) - Pipitone, N.; Notarnicola, A.; Levrini, G.; Spaggiari, L.; Scardapane, A.; Iannone, F.; Lapadula, G.; Zuccoli, G.; Salvarani, C.
Abstract : Background: MRI is often used to assess muscle inflammation in myositis. Muscle edema on short tau inversion recovery (STIR) sequences is thought to represent active inflammation. Dermatomyositis (DM) and polymyositis (PM) affect very frequently thigh muscles. However, it is unknown whether DM and PM differ in the respective involvement of the various thigh muscle groups. Objectives: To assess which thigh muscle groups are preferentially affected by DM and PM, respectively Methods: We analysed 72 patients from 2 Rheumatology centers, 31 with DM and 41 with PM diagnosed according to Bohan and Peter criteria. MRI edema (1= present, 0= absent) was assessed bilaterally on STIR sequences in 17 thigh/pelvic floor muscles. An MRI composite edema score (0-17) was calculated by adding the separate scores bilaterally and dividing them by two as described elsewhere (1). The (single measures) intraclass correlation coefficient (ICC) between the Radiologists involved was 0.78. Fisher's exact test was used for comparison of binomial data. Results: Age (years, mean ± SD) was similar in patients with DM (53±16) and PM (56±16). The F:M ratio was similar in DM (23/8) and PM (32/9). Disease duration (months, mean ± SD) was longer (20±31) in DM than in PM (52±68) (p=0.02). The frequency of the thigh muscle groups involved in DM and PM is shown in the Table below. Conclusions: Compared with PM, DM affects more frequently some muscle groups. Posterior muscle groups appear to discriminate poorly between DM and PM. These findings may be useful for differential diagnostic purposes in patients with histological features of DM without the typical skin rash as well as to target physiotherapy on more frequently affected muscles. Larger studies are needed to confirm our preliminary findings. The last 2 authors share senior authorship. References: Clin Exp Rheumatol 2012; 30:570-3. Disclosure of Interest: None declared